Further Research is Needed to Define the Benefits of Non-operative Rotator Cuff Treatment. Issue 3 (October 2016) - Kahlenberg, Cynthia A.; Dare, David M.; Dines, Joshua S.
Kukkonen et al.'s "Treatment of Nontraumatic Rotator Cuff Tears: A Randomized Controlled Trial with Two Years of Clinical and Imaging Follow-up" compared the efficacy of physical therapy, acromioplasty, and rotator cuff repair for the treatment of degenerative supraspinatus tendon tears in patients aged over 55. This review examines the authors' findings and their implications on clinical practice. Kukkonen et al. reported no significant difference in clinical outcome among patients treated operatively versus non-operatively for degenerative rotator cuff tears. The authors concluded that non-operative treatment is an appropriate option for patients aged 55 or older. Rotator cuff treatment outcomes are closely linked to patient age, and while this level I study found no evidence of a benefit of surgical treatment, the age range in the studied demographic was perhaps too wide to draw generalizable conclusions. Furthermore, 2-year follow-up may be inadequate to fully demonstrate the differences in outcomes between these treatment options.